A new species of Cephalocyclus (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico - Minor, Pablo; Dellacasa, Marco; Dellacasa, Giovanni (Zootaxa, 2015)
Cephalocyclus moroni new species (Coleoptera: Scarabaeidae: Aphodiinae) from humid forest in the mountains of Manantlán, Jalisco, Mexico is described and illustrated. It is similar to Cephalocyclus ordonezi Dellacasa, Dellacasa, & Gordon, 2007 and Cephalocyclus stebnickae Deloya & Ibañez-Bernal, 2000, both from Mexico.